Experiences of Well-Being in Retirement: A Phenomenological Study - Lukmanul Hakim; Ivon Arisanti (Universitas Katolik Soegijapranata, 2023)
Anxiety in retirement often arises in every individual because of a sense of worry that individuals have to leave their jobs to face retirement. This study aims to identify and describe the meaning of pension well-being for private employees and civil servants in Indonesia. This study conducted development interviews called subject-object interviews with twenty-five retirees consisting of 15 civil servants and ten private employees. The interviews were analyzed using Giorgi's phenomenological descriptive method. Based on this phenomenon, the findings of this study are divided into four: 1) Being grateful for health, 2) Giving meaning to life and society through new experiences, and 3) Being able to make choices independently and without ties to other people. People, 4) Creating positive family relationships. In this study, HARS scale results show that most of the respondent experience anxiety; this is indicated by physical, emotional, and mental/cognitive categories. These findings promote well-being in retirement by comprehensively describing the welfare phenomena experienced by retirees.